Neurosteroid Binding Sites on the GABAA Receptor Complex as Novel Targets for Therapeutics to Reduce Alcohol Abuse and Dependence - Mary W. Hulin; Russell J. Amato; Johnny R. Porter; Catalin M. Filipeanu; Peter J. Winsauer (Advances in Pharmacological Sciences)
Despite the prevalence of alcohol abuse and dependence in the US and Europe, there are only five approved pharmacotherapies for alcohol dependence. Moreover, these pharmacotherapeutic options have limited clinical utility. The purpose of this paper is to present pertinent literature suggesting that both alcohol and the neurosteroids interact at the GABAA receptor complex and that the neurosteroid sites on this receptor complex could serve as new targets for the development of novel therapeutics for alcohol abuse. This paper will also present data collected by our laboratory showing that one neurosteroid in particular, dehydroepiandrosterone (DHEA), decreases ethanol intake in rats under a variety of conditions. In the process, we will also mention relevant studies from the literature suggesting that both particular subtypes and subunits of the GABAA receptor play an important role in mediating the interaction of neurosteroids and ethanol.